2008
DOI: 10.1158/0008-5472.can-08-0206
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β Subverts the Immune System into Directly Promoting Tumor Growth through Interleukin-17

Abstract: Overexpression of the immunosuppressive cytokine transforming growth factor B (TGF-B) is one strategy that tumors have developed to evade effective immunesurveillance. Using transplantable models of breast and colon cancer, we made the unexpected finding that CD8+ cells in tumor-bearing animals can directly promote tumorigenesis, by a mechanism that is dependent on TGF-B. We showed that CD8+ splenocytes from tumor-bearing mice expressed elevated interleukin (IL)-17 when compared with naive mice, and that CD8+ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
199
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 227 publications
(209 citation statements)
references
References 52 publications
10
199
0
Order By: Relevance
“…Consistent with this finding, prior studies have shown that substantial IL-17 expression levels in human cancer tissues were correlated with increased vascularity [4,5]. Moreover, our findings are consistent with other reports that IL-17 directly influenced on the proliferation and survival of tumor cells and that IL-6-STAT3 pathway promoted tumor growth in IL-17-dependent manner [34,43]. However, it is an unresolved controversial issue whether IL-17 acts as a pro-or anti-tumor agent.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with this finding, prior studies have shown that substantial IL-17 expression levels in human cancer tissues were correlated with increased vascularity [4,5]. Moreover, our findings are consistent with other reports that IL-17 directly influenced on the proliferation and survival of tumor cells and that IL-6-STAT3 pathway promoted tumor growth in IL-17-dependent manner [34,43]. However, it is an unresolved controversial issue whether IL-17 acts as a pro-or anti-tumor agent.…”
supporting
confidence: 93%
“…In Although prior studies have reported that CD4 1 or CD8 1 T cells were implicated in IL-17 production in tumor-bearing hosts [3,34,35], these reports have not examined gd T cells. In our experiments, we showed that whereas small numbers of CD4 1 T cells produced IL-17, there were much more IL-17-producing gd T cells in the transplanted tumor tissues ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations